THE LEGAL POLICY STRATEGY OF THE APPLICATION 19 OF ANNEX "SAFETY MANAGEMENT" PRACTICE - V. D. Bordunov; B. P. Eliseev (Научный вестник МГТУ ГА, 2016)
The article analyzes a new Application 19 of "Safety Management", which contains the standards and recommended practices of ICAO, aimed at the establishment in member States of the ICAO uniform public systems of safety management on new principles and basis. It also analyzes the work to be undertaken of the Russian Federation on the redesign of its national system of aviation safety in accordance with the standards of Annex 19.